Optimalisasi Slide Power Point dengan Penerapan Metode Diskusi Kelompok dalam Meningkatkan Hasil Belajar PKN Tentang Keutuhan Negara Republik Indonesia pada Peserta Didik Kelas V Sekolah Dasar - Sukarti Sukarti (Universitas Sebelas Maret, 2021)
The purposes of this research are describing the optimization of slide power point inGroup Discussion Method in Civic Education learning about the Unity of Indonesian Republicon the five grade students of Bulu Elementary School on the First Semester 2016/2017Academic Year and analyzing the optimization of slide power point in Group DiscussionMethod toward to Civic Education learning result about the Unity of Indonesian Republic onthe five grade students of Bulu Elementary School on the First Semester 2016/2017 AcademicYear. This research is a Class Action Research (CAR). The subjects of this research are 16students. The results of this research are 1) the optimization of slide power point in GroupDiscussion Method is in a small group according to the sum and the characteristic of thestudents, 2) the optimization of slide power point in Group Discussion Method has thefunctions as the learning resource and learning media that showing relevant pictures with thesubject matter, 3) the application of Group Discussion Method in a small group is increasingthe students’ learning activities in discussion, answering the questions correctly and asking thefollowing questions, 4) the optimization of slide power point in Group Discussion Method hasthe same of group composition, so the students are not adapting with their group, 5) theoptimization of slide power point in Group Discussion Method is increasing the students’learning result, so qualified the minimal completeness criteria and minimal completeness at75%.